Alternative Origins to Interorganizational Trust: An Interdependence Perspective on the Shadow of the Past and the Shadow of the Future - Poppo, Laura; Zhou, Kevin Zheng; Ryu, Sungmin (Organization Science, 2008)
Despite the widespread acceptance of trust as an informal governance institution, our understanding of its origins is nascent. Our review of the literature identified two distinct explanations: Trust emerges from either a shadow of the past (i.e., prior history) or a shadow of the future (i.e., expectations of continuity). In this paper we develop and empirically examine a third perspective: The potential interdependence of these two explanations. Our results strongly endorse this third perspective. We find that prior history does not directly affect trust; instead, the observed positive relationship between the two is mediated by expectations of continuity. Consistent with this result, analyses further show that a longer prior history makes the effect of continuity on trust much stronger than a shorter prior history. We interpret these findings as suggesting: (1) the criticality and centrality of a shadow of the future (i.e., a forward-looking calculus) in generating trust in interorganizational exchanges and (2) that a shadow of the past plays a facilitating, albeit indirect, role in trust building. Our conceptual model also extends the conventional use of the transaction cost logic to show how reciprocal investments in asset specificity and uncertainty drive expectations of continuity, and consequently, interorganizational trust. Our results also show, unexpectedly, that prior history has a direct negative effect on trust after specifying the mediating path of continuity. Our moderation analysis indicates when this effect occurs: When weak expectations of continuity exist, trust is lower for exchanges characterized by a longer prior history, suggesting a potential darkside of overembedded ties.